Early Right Ventricular Function after Repair of Tetralogy Of Fallot: An Evidence-Based Study - Abdelhakim Mekkawy, Ahmed Mohamed; Ahmed, Faisal-Alkhateeb; Ghoneim, Ahmad Ahmed; Zahran, Ehab; Saad, Khaled; Malek, Ahmed Nabil; Ismail, Ahmed Ibrahim (Journal of Neonatal Surgery, 2025)
Background: Tetralogy of Fallot is a significant congenital heart disorder, and understanding its variants is crucial for pediatric cardiology management. Objectives: This research aimed to compare different surgical techniques that can be used to address RVOT (Right Ventricular Outflow Tract) reconstruction in Fallot Tetralogy repair regarding their influence on Right Ventricular function and immediate postoperative outcome. Methods: This is a prospective and evidence-based study; 60 children with TOF (Tetralogy of Fallot) were included. The main inclusion criteria are based on the children who undertook total repair between January 2019 and July 2021. Participants were assigned into three groups based on the surgical technique. In Group 1, no Transannular Patching was used; in Group 2A, Transannular Patching alone was used; and in Group 2B, Transannular Patching with mono-cusp construction was used. Moreover, preoperative and early postoperative assessments of Right Ventricular function were performed via pulse wave tissue Doppler imaging and conventional echocardiography. Assiut University's ethical committee granted ethical approval, and participants’ informed consent was also obtained to maintain confidentiality and ethical principles. Results: It was found that the three groups had no significant difference regarding mechanical ventilation time, inotrope duration, chest drain time, and total ICU stay. One month after surgery, RVSD (Right Ventricular Systolic Dysfunction) among Group 1 was observed in 6 patients (30%). Similarly, RVSD was found in Group 2A, with six patients (30%) and 10 patients (50%) in Group 2B. However, by the third month, none of the patients in any group exhibited RVSD. In contrast, RVDD (Right Ventricular Diastolic Dysfunction) was present in 10 patients (50%) in Group 1, 10 (50%) in Group 2A, and 18 (90%) in Group 2B at one month after surgery. In contrast, in the third month, no one in Groups 1 and 2A had RVDD, but it was persistent in eight patients (40%) in Group 2B. The severity of postoperative pulmonary regurgitation was generally increased in Group 2B (P < 0.001). IVA was negatively correlated with PRVCW/PVAD at one month (r = −0.22; P = 0.02) and three months (r = −0.21; P = 0.03) postoperatively. RV E/E′ was positively correlated with PRVCW/PVAD at one month after surgery (r = 0.61; P <0.001), while there was no significant correlation after three months. Conclusions: In this study, pulmonary valve preservation and TAP alone with limited incision techniques had good results regarding RV function and competency of PV. In contrast, TAP had no added value with mono-cusp construction.